Balancing Skill Education and General Education: A Study on Additional Skill Acquisition Programme of Kerala - Benson Davis
Skill development is a highly discussed subject in India in recent times. The government emphasises the skill development of youth, women, unemployed, persons with disabilities (PWDs) and workforce at large a priority. The skill development and educational policy of the government call for blending general education with vocational education and skill development. This research study seeks to understand the implications of the Additional Skill Acquisition Programme (ASAP), a scheme offered to higher secondary students of the Kerala, which runs simultaneously to the general academic curriculum. This study focuses on the impact of ASAP training on the general education of the enrolled students. The study found that the beneficiary students of ASAP training did not have any major negative impact on their general education due to the simultaneous skill education training received through ASAP. The English communication classes, as part of skill training, is also said to have helped them in their general education.